1994
DOI: 10.1007/bf02093783
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind crossover trial of metronidazole versus placebo in chronic unremitting pouchitis

Abstract: Metronidazole has been used to treat pouchitis, but there are no controlled data that show it is effective. Chronic unremitting pouchitis is a form of the disorder particularly difficult to manage. Diarrhea is the main symptom of pouchitis, which results from acute inflammation of the mucosa of an ileal reservoir. To test the hypothesis that metronidazole (400 mg thrice daily for seven days) is no better than placebo at reducing stool frequency in chronic unremitting pouchitis, a double-blind placebo-controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
145
1
9

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(158 citation statements)
references
References 14 publications
3
145
1
9
Order By: Relevance
“…Metronidazole in a dose of 400 mg three times daily ( 349 ) or 20 mg / kg per day ( 347 ) is eff ective in the treatment of chronic active pouchitis; in clinical practice, metronidazole in a dose of 250 mg three times daily is oft en used ( 329,349 ). Controlled trials showed at least similar effi cacy with ciprofl oxacin 500 mg twice daily ( 347 ), or with budesonide enema 2 g daily (not available in the United States) ( 350 ).…”
Section: Recommendations For the Management Of Pouchitismentioning
confidence: 99%
“…Metronidazole in a dose of 400 mg three times daily ( 349 ) or 20 mg / kg per day ( 347 ) is eff ective in the treatment of chronic active pouchitis; in clinical practice, metronidazole in a dose of 250 mg three times daily is oft en used ( 329,349 ). Controlled trials showed at least similar effi cacy with ciprofl oxacin 500 mg twice daily ( 347 ), or with budesonide enema 2 g daily (not available in the United States) ( 350 ).…”
Section: Recommendations For the Management Of Pouchitismentioning
confidence: 99%
“…Bacterial overgrowth occurs universally in pelvic pouches (3,4) yet patients with familial polyposis patients almost never develop pouchitis (1). Selected patients who develop pouchitis can be successfully treated with antibiotics, probiotics or even immune modulating agents (5)(6)(7)(8). Finally, diversion of the fecal stream in patients with refractory pouchitis is almost always successful (9).…”
Section: Introductionmentioning
confidence: 99%
“…6 In the second study, 13 patients with chronic pouchitis were treated in a double-blind crossover trial with metronidazole 400 mg three times daily or placebo for 14 days, and there was a signi®cant reduction in stool frequency with metronidazole. 7 In the latter study, 55% of the metronidazole-treated patients developed side-effects, including nausea, vomiting, abdominal discomfort and skin rash. Chronic administration of metronidazole at a high dose of 20 mg/kg per day for the treatment of Crohn's disease caused symptomatic peripheral neuropathy in up to 85% of patients, and is a limiting factor in using maintenance metronidazole to suppress chronic pouchitis.…”
Section: Discussionmentioning
confidence: 95%
“…5 There are only two placebo-controlled trials, both using metronidazole. 6,7 In one study a single patient with chronic pouchitis was treated in a blinded crossover`n of 1' trial with signi®cantly worse symptoms with placebo compared to metronidazole 250 mg daily. 6 In the second study, 13 patients with chronic pouchitis were treated in a double-blind crossover trial with metronidazole 400 mg three times daily or placebo for 14 days, and there was a signi®cant reduction in stool frequency with metronidazole.…”
Section: Discussionmentioning
confidence: 99%